Nonlinear graphene metamaterial - Papasimakis, Nikitas (2013)
We demonstrate that the broadband nonlinear optical response of graphene can be resonantly enhanced by more than an order of magnitude through hybridization with a plasmonic metamaterial, while retaining an ultrafast nonlinear response time of ∼ 1 ps. Transmission modulation close to ∼ 1% is seen at a pump fluence of ∼ 30 μJ/cm2 at the wavelength of ∼ 1.6 μm. This approach allows to engineer and enhance graphene’s nonlinearity within a broad wavelength range enabling applications in optical switching, mode-locking, and pulse shaping.